Physical Activity as a Modulator of Epicardial Adipose Tissue Dysfunction and Adipokine Profile in Obesity: Cardioprotective Mechanisms and Clinical Implications. A Literature Review - Lewandowska, Edyta; Król, Agata; Kwitowska, Patrycja; Łuczyński, Cezary; Muraszewska, Emilia; Muraszewski, Łukasz; Pyjecka, Małgorzata; Paczkowski, Maciej; Ubysz, Eryk; Wręczycki, Mariusz (Quality in Sport, 2026)
Background. Epicardial adipose tissue (EAT) is a metabolically active visceral fat depot surrounding the myocardium and coronary arteries, allowing locally secreted mediators to influence cardiac structure and function. In obesity, EAT expands and shifts from a cardioprotective to a pro-inflammatory and profibrotic phenotype, implicated in the coronary artery disease, atrial fibrillation and heart failure with preserved ejection fraction. Aim. To summarise current evidence on the effects of physical activity on EAT volume and adipokine secretion in patients with obesity and to outline the clinical implications of these relationships. Materials and methods. A narrative literature review was conducted using the PubMed/MEDLINE, Embase, and Cochrane Library databases. In total, 39 publications meeting predefined inclusion criteria – randomized controlled trials, systematic reviews, and meta-analyses – were analysed. Results. The reviewed studies show that endurance and resistance training markedly reduce epicardial adipose tissue (EAT) compared with non-exercise conditions. Evidence from quantitative syntheses suggests that this reduction is only partly explained by weight loss and aerobic, resistance, high-intensity interval and combined training programmes generally raise adiponectin levels, with high- intensity interval training (HIIT) producing the strongest effect. Conclusions. Structured physical activity lasting at least 12 weeks significantly reduces EAT volume and favourably modifies its adipokine secretion profile, partly independently of weight loss. These findings support physical activity recommendations in obesity that prioritise cardiometabolic risk reduction as the primary therapeutic goal rather than focusing solely on body-weight control.